The democratization of American Christianity - Hatch, Nathan O. (Yale University Press, 1989)
"In this prize-winning book Nathan O. Hatch offers a provocative reassessment of religion and culture in the early days of the American republic, arguing that during this period American Christianity was democratized and common people became powerful actors on the religious scene. Hatch examines five distinct traditions or mass movements that emerged early in the nineteenth century£the Christian movement, Methodism, the Baptist movement, the black churches, and the Mormons£showing how all offered compelling visions of individual potential and collective aspiration to the unschooled and unsophisticated"--